Pronase treatment improves flow cytometry crossmatching results. (28th June 2017) - Apithy, M.‐J.; Desoutter, J.; Gicquel, A.; Guiheneuf, E.; Westeel, P.‐F.; Lesage, A.; Piot, V.; Choukroun, G.; Guillaume, N.
Abstract : Flow cytometry crossmatching (FC‐XM) is the most sensitive cell‐based method for detecting donor‐specific antibodies in clinical organ transplantation. Unfortunately, background FC‐XM reactivity is elevated in assays with B lymphocytes—partly because of nonspecific immunoglobulin binding by Fc receptors and B‐cell surface immunoglobulins. To reduce the background reactivity in a B‐cell FC‐XM assay, we treated lymphocytes with pronase (1 mg/mL for 30 minutes). This treatment drastically reduced the presence of kappa light chains and Fc receptors (CD32b), while the concomitant decrease in CD19, CD20 and major histocompatibility complex (MHC) I and II expression on B‐cells was acceptable. Higher pronase concentrations (>2 mg/mL) started to significantly affect CD19, CD20, MHC‐I and ‐II expression on B‐cells. In subsequent prospective experiments (on 42 donor cells tested with 102 sera), we found that pronase treatment was associated with a relative increase of the sensitivity and specificity in our B‐cell FC‐XM assay.